2010
DOI: 10.1016/j.bbamem.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human cardiac KCNQ1/KCNE1 channel by epidermal growth factor receptor kinase

Abstract: The aim of the present study was to investigate whether/how the recombinant human cardiac I(Ks) could be regulated by epidermal growth factor receptor kinase in HEK 293 cells stably expressing hKCNQ1/hKCNE1 genes using the approaches of perforated patch clamp technique, immunoprecipitation and Western blot analysis. It was found that the broad spectrum isoflavone tyrosine kinase inhibitor genistein and the selective epidermal growth factor receptor kinase inhibitor tyrphostin AG556 suppressed the recombinant I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…This cell line has relatively small endogenous currents compared to the currents expressed in transfected cells (Figure 1), making contamination by endogenous currents insignificant. HEK 293 cells have been widely used to express cloned cardiac ion channels, including Nav1.5 [44], [45], Cav1.2 [46][48], Kv7.1 [49], Kv11.1 [31], [50], Kir2.1 [51] and Kv4.3 [52] channels. The currents exhibited in the present experiments are consistent with those reports.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line has relatively small endogenous currents compared to the currents expressed in transfected cells (Figure 1), making contamination by endogenous currents insignificant. HEK 293 cells have been widely used to express cloned cardiac ion channels, including Nav1.5 [44], [45], Cav1.2 [46][48], Kv7.1 [49], Kv11.1 [31], [50], Kir2.1 [51] and Kv4.3 [52] channels. The currents exhibited in the present experiments are consistent with those reports.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of hK v 1.5 channels by EGFR kinase activates the channel and may thereby enhance the current. However, orthovanadate did not affect I Kur /hK v 1.5 current or the channel phosphorylation level, which suggests the basal tyrosine phosphorylation of hK v 1.5 channels is saturated, as observed in rat cardiac K v currentS , human cardiac I to , hERG , I Ks (Dong et al, 2010), K ir 2.1 (Zhang et al, 2011a) and also hEAG1 and hSKCa1 (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
“…PTK-independent suppression by genistein has been previously observed in cardiac I Ks (Washizuka et al, 1998), I Kr (Missan et al, 2006), neuronal I Na (Liu et al, 2004), K ir 2.1 and K ir 2.3 channels (Zhao et al, 2008) and K v 4.3 channels expressed in CHO cells (Kim et al, 2011). However, PTK-dependent inhibition of human cardiac I Ks and hERG channels and hK ir 2.1, hK ir 2.3 and hK v 4.3 channels by genistein was revealed by the application of the protein tyrosine phosphatase inhibitor orthovanadate and the determination of tyrosine phosphorylation levels of these channel in our earlier reports Dong et al, 2010;Zhang et al, 2011aZhang et al, ,b, 2012. In this study, we found that genistein (3-100 μM) inhibited human atrial I Kur in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations